Contemporary Business and Economic Issues II - Aden, Abdishukri Rashid; Başar, Ufuk; Uyan, Umut; Duran, Hasan Engin; Yılmaz, Rabia; Yılmaz, Hüseyin; Özcan, Ahmet; Tekin, Bilgehan; Tekin, Nazlıhan (Academician Publishing Book DOI Portal, 2023)
Based in Ankara in Turkey, the independent academic publisher, Akademisyen Publishing House, has been publishing books for almost 30 years. As the directors of Akademisyen Publishing House, we are proud to publish more than 2700 books across disciplines so far, especially in Health Sciences. We also publish books in Social Sciences, Educational Sciences, Physical Sciences, and also books on cultural and artistic topics.